HUBUNGAN KOORDINASI MATA TANGAN DAN KELENTUKAN PERGELANGAN TANGANTERHADAP KETERAMPILANSERVIS PANJANGBULUTANGKIS PADA CLUB PB GARUDA BANDAR SUNGAI - Amelisa, Ria Mona; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This research was conducted with the aim to determine the relationship of eye hand coordination and wrist hand flexibilityto the skills of long servicebulutangcis at the PB Garuda Clubin Bandar Sungai. The problems found in this study are eye hand andwrist hand flexibilityare still not optimal, it isseen do badminton long service, thay arelook stiff when swinging wrist hand flexibility will be reduced then the ball is out of control again, losing direction of the goal so the ball hangs in and out to the side of the court. This research was conducted in the Jaya Mukti Hall. Jalan 4 Sehat 5 Sempurna, Kec.Sabak Auh, Siak district, Riau was conducted in Maretto September 2019. The sampling technique used in this study was total sampling, in which a total population of 8people was selected as a sample.Based on the results of the study that the author has described in the previous chapter, the following conclusions can be drawn: